Komunikasi Interpersonal dalam Menciptakan Intimacy pada Jalinan Asmara “TP” Di Facebook - Untung Eko Setyasari (KOMVERSAL, 2022)
This study aims to find out describing interpersonal communication through Facebook which can create intimacy relationships to develop into romance. This type of research is a qualitative research with a case study approach. Sources of data used in this study are primary and secondary data sources. The informant determination technique used is purposive sampling. Data collection techniques used are documents, interviews and observations. The results of this study indicate that the phenomenon of love between TP informants and their partners begins and develops from interpersonal communication on Facebook. Facebook has become a place that accommodates interpersonal communication between informants and their partners so that it creates intimacy in their relationship and ends in commitment (dating). In addition, in this phenomenon there are also stages that informants go through when establishing relationships with their partners by online, ranging from curiosity, investigation, testing, increasing contact frequency, anticipation, fantasy integration, to the decision to commit. The results of this study can provide an overview of the parties who also experienced the same thing as the informant. As a result, they can maintain their intimate relationship, be wiser in using Facebook so that they can anticipate unwanted things as a result of using social media.